Designing a Tele-pediatric System based on the internet - Nourelhuda Ali Yousif Mohamed; Mohammed Yaqoob Ismail (Open Journal of Pediatrics and Child Health - Peertechz Publications, 2022)
The outgrowth and quick development in telecommunication technologies have opened new opportunities for diagnosing many diseases, which are life-threatening, for patients who are in rural areas and districts far away from the city, and where there are no specialists. Critical and life-threatening diseases, in which the patient cannot wait until going to a central hospital, or specialist, need to benefit from the advantages of telecommunication technologies to save the patient's life. The segment of pediatric patients represents a significant number of patients and children represent the country's present and bright future, so we must focus on the importance of diagnosing and treating their diseases early and on a time using the ways and means available to protect their lives from risks. Designing a tele-pediatric system for monitoring such cases can be vital and efficient in saving those babies' lives and protecting them from significant risks of disability and even death that happen if their defects are not diagnosed and treated soon after birth. This project aimed to design a tele-pediatric system, using webpages at both transmitting and receiving sites and connected to a united database and then linked with the Sudan University of Science and Technology's Network for testing its efficiency and effectiveness. If this project is applied; it will contribute to saving the baby's life and raise the overall health care.